1992
DOI: 10.1542/peds.89.4.643
|View full text |Cite
|
Sign up to set email alerts
|

Cerebroelectrical Depression Following Surfactant Treatment in Preterm Neonates

Abstract: During surfactant treatment of respiratory distress syndrome, 23 premature newborns were investigated with continuous amplitude-integrated electroencephalography (cerebral function monitors). Simultaneously, arterial blood pressure and transcutaneous blood gas values were recorded. A short(<10 minutes) but significant decrease in cerebral activity was seen in almost all neonates immediately after the surfactant instillation, in spite of an improved pulmonary function. In 21 of 23 neonates, a transient f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(11 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Interestingly, the use of poractant alfa, which has been reported previously to be clinically superior to beractant, led to more pronounced depression of the aEEG signal. Decrease of cerebral activity lasting up to 24 h despite improvement of pulmonary function after SRT has been reported before with various preparations and techniques of administration [ 5 8 ]. One of the proposed mechanisms leading to this phenomenon is a rapid decrease in pulmonary vascular resistance after SRT.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Interestingly, the use of poractant alfa, which has been reported previously to be clinically superior to beractant, led to more pronounced depression of the aEEG signal. Decrease of cerebral activity lasting up to 24 h despite improvement of pulmonary function after SRT has been reported before with various preparations and techniques of administration [ 5 8 ]. One of the proposed mechanisms leading to this phenomenon is a rapid decrease in pulmonary vascular resistance after SRT.…”
Section: Discussionmentioning
confidence: 89%
“…desaturation. It has been shown that surfactant replacement therapy (SRT) may cause acute changes in cerebral oxygenation and suppression of bioelectrical activity measured with amplitude-integrated electroencephalography (aEEG) [ 5 9 ]. Varying physiologic responses with different surfactant preparations have been observed in an animal model [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another common procedure that usually affects aEEG trace is surfactant administration, which often can lead to a noticeable but transient depression on brain activity lasting around ten minutes. 65 …”
Section: Revisionmentioning
confidence: 99%
“…Although some studies suggested overall benefits of the InSurE procedure, 12 other studies failed to prove these benefits in that regard. 13…”
Section: Introductionmentioning
confidence: 99%
“…Although some studies suggested overall benefits of the InSurE procedure, 12 other studies failed to prove these benefits in that regard. 13 In view of this, different methods of MIST have been introduced for evaluation: intra-amniotic instillation, 14 pharyngeal instillations, 15 administrations via laryngeal mask airway (LMA), 16 and nebulized surfactant administration in spontaneously breathing infants. 17 Other types of MIST using tracheal catheterization were described; the surfactant is given to spontaneously breathing premature infants via feeding tube 18,19 or vascular catheter 20 placed in the trachea only during surfactant administration, and removed thereafter.…”
Section: Introductionmentioning
confidence: 99%